Evaluation of mechanical properties of additively manufactured beams with lattice structures - Pir, İnci; Şahin, Serhat Arda; Tüfekci, Mertol; Tufekci, Ekrem (American Society of Mechanical Engineers, 2024)
The use of lattice structurses is becoming more common day by day. Limitations such as being expensive and time-consuming have led to a search for new solutions in the industry. In light of these limitations, the widespread use of 3D printing technology methods is evaluated. 3D printing technology has advantages in terms of design flexibility, quick prototyping, lightness and the ability to produce complex shapes. 3D printing is used to systematically investigate different geometries in line with the requirements of sustainable product development, leading to the production of auxiliary structures that are both strong and lightweight. This research investigates the mechanical properties of various lattice structures that were previously modelled and analysed through analytical methods in the literature. The samples with five different auxetic structures are manufactured using the Fused Deposition Modelling (FDM) 3D printing technique, with Acrylonitrile Butadiene Styrene (ABS) as the selected material. The manufactured samples are subjected to a three-point bending test to assess their mechanical characteristics, including the flexural modulus, flexural strength, and elongation at break, and the effect of the in-plane geometry on the mechanical behaviour is evaluated.
Proceedings of ASME Turbo Expo 2024 : Turbomachinery Technical Conference and Exposition (GT2024), June 24-28, 2024, London, United Kingdom
Keywords: additive manufacturing; lattice structures; three-dimensional printing; 3D printing; beams; three-point bending test